Compliance With Recommendations of the Surveillance, Epidemiology, and End Results (SEER) Treatment Data Use Agreement: A Review of Published Studies - Hong, Yoon Duk; Mariotto, Angela B; Lewis, Denise R; Noone, Anne-Michelle; Howlader, Nadia; Scoppa, Steve; Feuer, Eric J (Medical care, 2025)
The Surveillance, Epidemiology, and End Results (SEER) Program collects data on the first course of cancer treatment, but no and unknown receipt of treatment cannot be distinguished for radiation therapy (RT) and chemotherapy. As part of the Data Use Agreement (DUA), users must acknowledge that they understand the data limitations and agree to include a description of the limitations in any analyses published using the data. The objective of this review was to evaluate users' compliance with the recommendations of the DUA. Publications from a PubMed search were matched with the names of SEER treatment data users, and keywords were applied to identify relevant studies. Five reviewers (with 2 per publication) independently assessed if the authors (a) conducted analyses supported by these data, (b) correctly labelled no/unknown treatment as "no/unknown", and (c) described the limitations of their use. Publications were classified as "followed recommendations", "partially followed recommendations", or "did not follow recommendations" of the DUA. Among a total of 120 studies included in the review, 106 (88.3%) studies did not follow recommendations, 11 (9.2%) partially followed recommendations, and 3 studies (2.5%) followed recommendations. Only 11.7% of publications correctly labelled the "no/unknown" category as "no/unknown", and described the limitations associated with the no/unknown issue. In this review, we found substantial misuse of the SEER treatment data and limited acknowledgement of the limitations of the SEER treatment data in publications. Such findings highlight the need to think of effective ways of encouraging appropriate use of the treatment data.